Peran Probiotik Terhadap Kesehatan Saluran Pencernaan dan Produktivitas Sapi Perah: Literatur Review - Mulyani, Mila; Handini, Aulia Tri; Salsabila, Winda; Sutanto, Ridwan Hakim; Ilyas, Gian Wiguna; Nurrofingah, Ulfa; Nafisah, Ainun (Jurnal Sains Peternakan Nusantara, 2025)
Probiotics are live microorganisms that have significant benefits for the health of ruminant livestock, especially dairy cattle, when administered in sufficient amounts. The use of probiotics in the modern livestock industry has been proven to improve digestive efficiency, stabilize rumen microflora, and increase milk productivity. Previous research indicated that probiotic strains such as Bacillus subtilis, Lactobacillus spp. dan Saccharomyces cerevisiae play an important role in improving rumen fermentation, increasing dry matter digestibility, and suppressing the growth of pathogenic microbes. The cow's digestive system begins in the mouth, then the food enters the esophagus to the rumen for fermentation, then to the omasum for water absorption, to the abomasum (true stomach), small intestine, large intestine, and then excreted. This review aims to analyze various research findings regarding the role of probiotics in the gastrointestinal health and productivity of dairy cattle, based on 20 nationally and internationally accredited scientific articles (SINTA 2 - 5 and Scopus) published between 2016 - 2025. The results of the study show that routine administration of probiotics can improve rumen health, increase feed conversion efficiency, and lead to significant increases in milk production and quality without negative effects on the livestock.